Modeling Melanoma Heterogeneity In Vitro: Redox, Resistance and Pigmentation Profiles - Larissa Anastacio da Costa Carvalho; Isabella Harumi Yonehara Noma; Adriana Hiromi Uehara; Ádamo Davi Diógenes Siena; Luciana Harumi Osaki; Mateus Prates Mori; Nadja Cristhina de Souza Pinto; Vanessa Morais Freitas; Wilson Araújo Silva Junior; Keiran S. M. Smalley; Silvya Stuchi Maria-Engler (MDPI AG, 2024)
Microenvironment and transcriptional plasticity generate subpopulations within the tumor, and the use of BRAF inhibitors (BRAFis) contributes to the rise and selection of resistant clones. We stochastically isolated subpopulations (C1, C2, and C3) from naïve melanoma and found that the clones demonstrated distinct morphology, phenotypic, and functional profiles: C1 was less proliferative, more migratory and invasive, less sensitive to BRAFis, less dependent on OXPHOS, more sensitive to oxidative stress, and less pigmented; C2 was more proliferative, less migratory and invasive, more sensitive to BRAFis, less sensitive to oxidative stress, and more pigmented; and C3 was less proliferative, more migratory and invasive, less sensitive to BRAFis, more dependent on OXPHOS, more sensitive to oxidative stress, and more pigmented. Hydrogen peroxide plays a central role in oxidative stress and cell signaling, and PRDXs are one of its main consumers. The intrinsically resistant C1 and C3 clones had lower MITF, PGC-1α, and PRDX1 expression, while C1 had higher AXL and decreased pigmentation markers, linking PRDX1 to clonal heterogeneity and resistance. PRDX2 is depleted in acquired BRAFi-resistant cells and acts as a redox sensor. Our results illustrate that decreased pigmentation markers are related to therapy resistance and decreased antioxidant defense.